Integrated teaching methodology in the development of foreign language professional communicative competence on the discipline “organic chemistry” at Kazakhstan University - Kenzhe, Aziza; Bitemirova, Aliya; Bayan, Ualikhanova; Bitursyn, Saule; Zhorabekova, Ainur (Frontiers in Education, 2025)
IntroductionIn Kazakhstan, acquiring a foreign language is a prerequisite for advancing chemistry education, enabling students to access global scientific advancements, establish international professional connections, and exchange knowledge. This study examines the implementation of CLIL/ICLHE to enhance foreign language professional communicative competence (FLPCC) in chemistry. Based on this approach, a training model and a set of exercises were developed.MethodsA quasi-experimental design was employed to compare the results among third-year students enrolled in the “Chemistry Teacher Training” educational program divided into experimental and control groups through pre-test and post-test assessments. The experimental group received training based on modeling, while the control group received traditional teaching. The experimental set of exercises was implemented during the 5 and 6th semesters of the academic year. The experiment consisted of three stages: preparation stage, forming stage and verifying stage.ResultsAll data were analyzed using the independent samples t-test. The mean values and standard deviations for each criterion were evaluated in the control and experimental groups. The initial pre-test analysis indicated no significant differences between the groups, validating the equivalence of their baseline levels. However, after conducting the experiment, the results showed that the experimental group outperformed the control group across all measured criteria. These findings suggest that the proposed methodology positively influenced the development of various skills in students.DiscussionThe set of exercises was piloted during the experiment, and its effectiveness was evaluated through a comparison of pre-test and post-test results. The analysis using the t-test revealed a developmental trend across all criteria for the FLPCC components compared to the initial levels. However, one limitation of CLIL/ICLHE approach is that a single lesson may be insufficient to fully cover a single topic due to the extensive number of tasks involved. This limitation highlights the need for additional instructional time.